2016
DOI: 10.22159/ijcpr.2016v8i4.15279
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Activity of Some Indian Medicinal Plants

Abstract: Objective: The current study is carried out to evaluate cytotoxicity activity of the methanolic extracts of some medicinal (Buchanania axillaris Desr, Tamilnadia ulignosa Retz, Phaseolus semierectus L and Stylosanthes fruticosa Retz).Methods: Cytotoxicity activity was evaluated on human cancer cell lines such as lung cancer (A549) and skin cancer (A431) using MTT assay method. Results:The selected plant extracts showed the dose-dependent cytotoxicity activity on the tested cell lines. The cytotoxicity variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The results indicated that P. discoridis had the highest antitumor activity against the human skin tumor cell line (A431). The obtained results are supported by previous studies where plant extracts rich in flavonoids had a strong inhibition of the growth of A431 cell lines (Mohansrinivasan et al, 2015;Neerugatti et al, 2016;Zeng et al, 2018). Also, the anti-skin cancer activity of P. discoridis was higher than that of the standard chemotherapeutic drug (doxorubicin).…”
Section: Discussionsupporting
confidence: 85%
“…The results indicated that P. discoridis had the highest antitumor activity against the human skin tumor cell line (A431). The obtained results are supported by previous studies where plant extracts rich in flavonoids had a strong inhibition of the growth of A431 cell lines (Mohansrinivasan et al, 2015;Neerugatti et al, 2016;Zeng et al, 2018). Also, the anti-skin cancer activity of P. discoridis was higher than that of the standard chemotherapeutic drug (doxorubicin).…”
Section: Discussionsupporting
confidence: 85%
“…For primary (nondividing) cells, drug sensitivity is measured as enhanced cell kill of treated cells as compared to the loss of cells already commonly seen in untreated cells. This experiment is designed based on different research paper review [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, natural product and imitative from the natural product as a new anticancer drug and antibiotics are permitted by US Food and Drug Administration (FDA) [8][9][10]. Natural products mostly from plant source have an important basis for discovering new bioactive components with few side effects and high efficacy [11]. Anticancer properties have been revealed against a broad range of cancers by numerous foods, for example, grains, cereals, spices, vegetables, and medicinal plants and their bioactive compounds [12].…”
Section: Introductionmentioning
confidence: 99%